The Layout Planning At Sehati Dua Minimarket, Ciawigebang, Kuningan: Market Basket Analysis and Activity Relationship Chart Approach - Ramdhani, Edwin; Awaluddin, Robi; Suhardi, Dadang (LPPM Universitas Bina Bangsa, 2021)
The layout is one of the factors that affect visitor satisfaction. Where a good design will be the face of the company itself. There is a layout problem in the Sehati minimarket location where the product arrangement displayed has not been neatly arranged. The display of goods is placed directly on the floor without using any shelves. One way to optimize the relationship between product group proximity and use of space or layout. This research uses Market Basket Analysis and Activity Relationship Chart method by measuring three kinds of quantitative measures, namely support (factor domination level), confidence (factor level) and the ratio of improvement (viability factor proximity) and relationship product proximity qualitatively. Results of data processing and analysis with the method of MBA and Tolls ARC approach there are several alternatives to the new layout improvement then selected on of the best choice by the management company with a value of 40, and some changes from the previous layout the product – the product that must be moved among product with value the smallest, and development with an enormous support value,(1) namely The Gelas products